Identification of Environmental Cues and Decision-Making Strategies of Residential Burglars - So-Yeon Park; Kyung-Hoon Lee (International Journal of Architectural Engineering Technology, 2018)
In this study, as a preliminary study for a development of a residential burglars’ target selection model, previous studies on residential burglars’ target selection were reviewed and analyzed in terms of methods and purposes of research, and the implications for future research were suggested by integrating the results of the review. Firstly, it seems that the experimental research method has many advantages for developing the target selection model at the house level compared to using crime data and conducting interviews or questionnaires. Secondly, virtual reality can be used as an effective tool in the experiment, since it allows researchers to construct the experimental environment without any constraint and enables participants to be completely immersed. Thirdly, although researchers in the field of architecture tend to mainly focus on deriving environmental cues that influence the decision of the burglar, decision-making strategies used by burglars when selecting targets should also be identified to develop a comprehensive model of burglars’ target selection. Finally, considering the cognitive process of residential burglar, several research questions can be derived (i.e. ‘What environmental cues do burglars consider when evaluating each environmental attribute?’, ‘What decision-making strategy do burglars use to evaluate each environmental attribute?’, and ‘What decision-making strategy do burglars use to make a decision on whether or not to commit burglary?’).